Development and optimization of curcumin analog nano-bilosomes using 21.31 full factorial design for anti-tumor profiles improvement in human hepatocellular carcinoma: in-vitro evaluation, in-vivo safety assay - Haidy Abbas; Yasmin A. El-Feky; Majid Mohammad Al-Sawahli; Nehal M. EL-Deeb; Hala Bakr El-Nassan; Mariam Zewail (Taylor & Francis Group, 2022)
Curcumin (CU) is a natural polyphenolic phytoingredient. CU has anti-inflammatory, anti-oxidant, and anticancer activities. The poor solubility, bioavailability, and stability of CU diminish its clinical application. Hence, structural modification of CU is highly recommended. The CU analog; 3,5-bis(4-bromobenzylidene)-1-propanoylpiperidin-4-one (PIP) exhibited high stability, safety, and more potent antiproliferative activity against hepatocellular carcinoma. In the present study, nano-bilosomes (BLs) were formulated to augment PIP delivery and enhance its solubility. A 21.31 full factorial design was adopted to prepare the synthesized PIP-loaded BLs. Optimized F4 showed a biphasic release pattern extended over 24 h, with EE%, ZP, and PS of 90.21 ± 1.0%, −27.05 ± 1.08 mV, and 111.68 ± 1.4 nm. PIP-loaded BLs were tested for safety against a non-cancerous cell line (Wi-38) and for anticancer activity against the Huh-7 human hepatocellular carcinoma cells and compared to the standard anticancer drug doxorubicin (Dox). The anticancer selectivity index of PIP-loaded BLs recorded 420.55 against Huh-7 liver cancer cells, markedly higher than a CU suspension (18.959) or the Dox (20.82). The antiproliferative activity of nano-encapsulated PIP was roughly equivalent to Dox. PIP-loaded BLs, showed enhanced drug solubility, and enhanced anticancer effect, with lower toxicity and higher selectivity against Huh-7 liver cancer cells, compared to the parent CU.